2019
DOI: 10.3390/ijerph16112021
|View full text |Cite
|
Sign up to set email alerts
|

The Tolerance Characteristics of Resident Fish in the Upper Yangtze River under Varying Gas Supersaturation

Abstract: In circumstances where total dissolved gas (TDG) levels are variable, the peak TDG and duration are expected to be the dominant drivers of fish survival. Focusing on the peak TDG and duration in natural rivers, a laboratory experiment and field experiments in the upper Yangtze River were conducted with Prenant’s Schizothoracin (Schizothorax prenanti), a rare species inhabiting the upper Yangtze River, to examine the tolerance characteristics of fish under varying gas supersaturation levels. The results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Research on tolerances to TDG has so far focused on fish species from China and North America. Several field-and laboratory studies on the impact of and tolerance to TDG on endemic fish species have been conducted during the recent years in China (Wang et al, 2015;Cao et al, 2019;Ji et al, 2019;Xue et al, 2019;Deng et al, 2020). These studies were conducted due to sharp declines in several endemic fish populations after construction of hydropower constructions, and indicate that the tolerance to TDG vary among fish species.…”
Section: Introductionmentioning
confidence: 99%
“…Research on tolerances to TDG has so far focused on fish species from China and North America. Several field-and laboratory studies on the impact of and tolerance to TDG on endemic fish species have been conducted during the recent years in China (Wang et al, 2015;Cao et al, 2019;Ji et al, 2019;Xue et al, 2019;Deng et al, 2020). These studies were conducted due to sharp declines in several endemic fish populations after construction of hydropower constructions, and indicate that the tolerance to TDG vary among fish species.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated that high levels of TDG supersaturation result in the increasing mortality of fish [40,41]. Ji et al [42] reported that Prenant's schizothoracin had higher mortality at high TDG levels (130% and 135%) than at low TDG levels (110% and 115%). Some researchers found that the tolerance of Chinese sucker decreased with increasing TDG levels [22,43].…”
Section: Discussionmentioning
confidence: 99%
“…In natural rivers, TDG supersaturation is often caused by a change of water temperature (Bouck, 1984) and water falling (Rowland & Jensen, 1988). Dammed rivers can occur severe TDG supersaturation caused by flood discharge during flooding seasons (Figure 6a), resulting in serious impacts on fish downstream (Ji et al., 2019; Pulg et al., 2016). For instance, the Chief Joseph Dam released flow in excess of the 110% TDG compliance criterion (EPA, 1987) in the Columbia River, causing the downstream Wells Dam to be unable to comply with water quality criteria for 125 of 133 compliance‐mandated days in 2012 (Witt et al., 2017).…”
Section: River Damming Impacts On Fish Physical Habitatmentioning
confidence: 99%